2016
DOI: 10.1128/jcm.00516-16
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-Loaded Bone Cement Does Not Negatively Influence Sonicate Fluid Culture Positivity for Diagnosis of Prosthetic Joint Infection

Abstract: We compared culture results to investigate the influence of antimicrobial-loaded cement on sonicate fluid culture positivity for the diagnosis of prosthetic joint infection. Fifty-four subjects were assessed. The sensitivities of sonicate fluid culture were 77.8% (14 of 18) in subjects with an antimicrobial-loaded cemented prosthesis and 58.3% (21 of 36) in subjects with an antimicrobialfree prosthesis. With the increasing number of lower-extremity total joint arthroplasty surgeries, there has been an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We previously demonstrated the in vitro efficacy of PG-CSH beads loaded with a broad-spectrum antibiotic combination of vancomycin and tobramycin in combination against key gram-positive organisms associated with PIs [19]. The incorporation of tobramycin in combination with vancomycin permits broad spectrum activity against gram-negative pathogens as well and is frequently used in eluting acrylic and mineral cements for dead space management or mechanical function [30][31][32][33][34][35]. Given the increased risk of failure and reduced success rate for therapeutic intervention associated with gram-negative pathogens in PIs, we evaluated this antibiotic combination loaded into PG-CSH beads against K. pneumoniae, A. baumannii and P. aeruginosa biofilm formation and established biofilms in order to better characterise the in vitro antibacterial and antibiofilm efficacy of PG-CSH beads [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated the in vitro efficacy of PG-CSH beads loaded with a broad-spectrum antibiotic combination of vancomycin and tobramycin in combination against key gram-positive organisms associated with PIs [19]. The incorporation of tobramycin in combination with vancomycin permits broad spectrum activity against gram-negative pathogens as well and is frequently used in eluting acrylic and mineral cements for dead space management or mechanical function [30][31][32][33][34][35]. Given the increased risk of failure and reduced success rate for therapeutic intervention associated with gram-negative pathogens in PIs, we evaluated this antibiotic combination loaded into PG-CSH beads against K. pneumoniae, A. baumannii and P. aeruginosa biofilm formation and established biofilms in order to better characterise the in vitro antibacterial and antibiofilm efficacy of PG-CSH beads [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of fluid used for sonication of the ACSs was not measured, and patients were also receiving systemic antibiotics at the time of explantation of the ACS, factors that could additionally or alternatively affect culture results. On the other hand, a study performed by our group showed that antimicrobialloaded cement used for the fixation of the prosthesis did not negatively impact sonicate fluid culture of the explanted prostheses (27). It is possible that even if sonication increases the release of antimicrobials from ACSs, the lactated Ringer's used in our study for the sonication of ACS could have diluted the antimicrobial agents and that the concentration step used may have facilitated microbial growth in sonicate fluid cultures; however, in our study, sonicate fluid was not specifically assayed for antimicrobial concentrations.…”
Section: Discussionmentioning
confidence: 86%
“…This could lead to false negative sonication results during the diagnostics of PJI. Other studies however, see no interference in the diagnostics of PJI using sonication and antibiotic loaded PMMA 19 . Thus further clarification on using sonication fluid from sonicating standardized antibiotic loaded PMMA scaffolds, to diagnose PJI, is needed.…”
Section: Introductionmentioning
confidence: 86%